Business Law Futurism: Between Market Rationality and Human - Kurniawan, Komang Suputra; Sudharma, Kadek Januarsa Adi; Kurniawan, I Gede Agus (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The rise of digital technologies has brought substantial changes to the way business is conducted, regulated, and understood. As companies increasingly rely on algorithmic systems, data-driven decisions, and platform-based markets, business law is pushed to evolve beyond its conventional functions. Yet, these rapid changes also reveal a growing gap: while market efficiency continues to advance, the ethical and human dimensions of law risk being overshadowed. This study explores how business law can remain relevant and principled in the midst of these shifts, especially when technological progress challenges long standing legal assumptions about responsibility, fairness, and accountability. In today’s digital economy, legal norms no longer operate solely through state regulation. Instead, they intersect with platform rules, automated systems, and global standards that influence behaviour as strongly as formal law—sometimes even more. This blending of authorities creates real uncertainty: Who is accountable when algorithms decide outcomes? How can ethical considerations be upheld when market logic prioritises speed over reflection? These questions underline the need for a more grounded understanding of how law should respond to technological acceleration. This article argues that the future strength of business law lies in restoring its ethical orientation while still embracing innovation. Law must continue to protect human dignity, ensure fairness, and maintain transparency, even as markets demand efficiency. Rather than treating technology as something that diminishes the role of law, this study views law as a guide that should shape the direction of technological development. By strengthening its moral foundation, business law can adapt to digital transformation without losing its core purpose. Ultimately, the article emphasises that progress should not come at the cost of justice, and that a human-centred legal system remains essential in navigating the complexities of modern economic life.